The Analysis of the Art Ecosystem in the Development of Musicmathematics - Samuel, Samuel; Mudra, I Wayan; Sariada, I Ketut (Journal of Aesthetics, Creativity and Art Management, 2025)
Musicmathematics is the integration of mathematical principles in music, offering a new approach in contemporary music composition. This study arises from the urgency to understand the impact of musicmathematics on the art ecosystem holistically, encompassing cultural, social, economic, educational, legal, and technological aspects. The research employs document analysis and audiovisual analysis methods to identify patterns, relationships, and the influence of musicmathematics on various elements of the art ecosystem. The study is based on the art ecosystem theory by Becker (1982), which emphasizes the interaction between art actors and social structures, and Benoît Mandelbrot’s fractal theory (1989), which observes recurring patterns in music structures. Additionally, the concept of dynamic culture (Geertz, 1973a) is used to understand cultural transformation through the application of mathematical innovations. The results of the research indicate that musicmathematics significantly contributes to music composition innovation, despite facing challenges in social acceptance and commercialization. Culturally, musicmathematics creates tension between innovation and tradition; socially, this genre forms a limited experimental community; and in education, it enriches curricula with analytical approaches facilitated by technology. The study concludes that musicmathematics holds great potential in supporting the transformation of contemporary arts, particularly through strengthening education and technology. However, adaptive strategies are needed to increase the acceptance of this concept in a broader art ecosystem. Keywords: musicmathematics, art ecosystem, music innovation, music education, art technology.